Filip Melanchton. Feniks Reformacii͏̈. Petro Kotljarov = Philip Melanchthon. Phoenix of the Reformation by Petro Kotliarov - Kondor, Tymofij (Bogoslovs'ki rozdymi, 2021)
New edition review: Філіп Меланхтон. Фенікс Реформації. Петро Котляров. К.: Дух і Літера, 2020. 328 с.; ISBN 9789663787602 (тверда обкл.); 250 UAH.